Provision of recommended antenatal care services in Ethiopia: missed opportunity for screening and counselling - Abdulaziz Mohammed Hussen; Martin Heine; Maria Barreix; Rosemary K. Muliokela; Tigest Tamrat; Özge Tunçalp; Binyam Tilahun; Diederick E. Grobbee; Joyce L. Browne (BMC Pregnancy and Childbirth)
Abstract Background Utilisation of Antenatal care (ANC) in Ethiopia has shown a steady increase in the last two decades, from 27% in 2000 to 74% in 2019. While it is encouraging to see more women attending and receiving ANC, attention to ensuring the quality of the ANC services provided to the visiting women is important. Therefore, this study aimed to assess the provision of recommended ANC services and to identify client related factors associated with the provision of the services. Methods The study was conducted using the 2019 Ethiopian Demographic and Health Survey (EDHS) data. Provision of recommended ANC services was assessed for the EDHS sub-set of 1573 women who had a live birth in the two years preceding the survey and at least one ANC visit. Four components of ANC (i.e. blood pressure measurement, blood and urine test, and counselling on signs of pregnancy complications) were used to measure the provision of recommended ANC services. Bivariable and multivariable analysis was performed to identify client related factors associated with the provision of recommended ANC services. An adjustment was made to account for the complex survey design throughout the analysis (weight, stratification, and clustering). Results About one in two women (49.7%; 95% CI: 44.6–55.0) reported receiving the four components of ANC during their pregnancy. Having a higher educational level (adjusted Odds Ratio [aOR] = 2.84; 95%CI: 1.15–6.97), being in the middle (aOR = 1.87;95% CI: 1.14–3.06), richer (aOR = 2.56; 95% CI: 1.46–4.49), and richest (aOR = 4.21;95% CI: 1.93–9.21) wealth quintiles, and having two to three (aOR = 5.40;95% CI: 2.00-14.60) and four or more (aOR = 13.45; 95% CI: 4.81–37.58) ANC visits were client related factors associated with the provision of recommended ANC services. Conclusion Despite the high ANC1 coverage, only one in two women reported receiving the four recommended services. To produce the desired health outcome from ANC utilisation, expanding the coverage should be accompanied by a strong focus on the contents and quality of care. Moreover, regardless of their educational and economic status, all women should receive all components of care as per the recommendations.